Українська книга як засіб національно-культурного відродження 1917-1920 рр.: аспект державної підтримки друку - Hrynivskyi, Taras (Київський національний університет культури і мистецтв, 2018)
У статті розглянуто розвиток українського книговидання 1917–1920 рр., а також заходи різних урядів на його підтримку, проаналізовано їхню результативність. The author of the article studies the processes taking place in publishing in Ukraine at the time of Ukrainian revolution, analyzes positive and negative tendencies, problems, failures and factors that caused them. The author sets and carries out the tasks to analyze the situation with national publishing in the 1917–1920s, to formulate the key-aspects in publishing sphere of state policy of different governments, to specify the results of government programs implementation. The beginning of the 1917th witnesses stormy growth of national publishing if compared with previous years, no matter which politicians came to power. All the pro-Ukrainian governments understood the importance of printed word for national statehood development and made every offort to support Ukrainian publishing, paying special attention to schoolbooks and belles-lettres. Notwithstanding extreme financial situation, the majority of governments tried to support publishing houses, facilitating the development of Ukrainian-language book publishing not only in the country itself, but beyond its borders as well. The author of the article states, that the 1918-1919s were the most fruitful years for Ukrainian language book publishing due to well-thought-out protectionist policy of Ukrainian governments in the times of Central Council (Rada) and Hetmanship . Starting with 1919 one can obser ve the growth of Russian-language printed products segment and in 1920 its development becomes stable. This is the period when Bolsheviks came to power.
UKRAINIAN BOOK AS THE MEANS OF NATIONAL CULTURAL RENEWA L IN THE 1917–1920s: THE ASPECT OF STATE SUPPORT OF THE PRINTING
Keywords: українське книгодрукування, державна підтримка друку, статистика друку.; Ukrainian publishing, state support of publishing, publishing statistics